CUSTOMER RELATIONSHIP MANAGEMENT : STUDI KASUS PERPUSTAKAAN INSTITUT TEKNOLOGI DEL - TIURMA LUMBANGAOL (LP2MTBM MAKARIOZ, 2019)
Customer Relationship Management is very important to be applied in libraries to increase the number of library visitors. The purpose of this study is to examine the efforts that need to be made to improve library management in a better direction. The method of observing the system is done by trying menus on the library information system. Currently the Del Institute of Technology Library has not conducted customer relationship management. The Del Institute of Technology library always strives to increase the satisfaction of library service users. In an effort to improve visitor services, the IT Del Library will make changes to the information system used so that the information system used can be more easily understood by users of library services. Some things that are done are improving the existing system, changing the system design and making additional menus for institutional repositories. Personalization of library service users can be done so that what is currently needed and in the future can be known and finally served by the library to its customers or users. It can happen through customer relationship management.